Does Minority Representation in Police Agencies Reduce Assaults on the Police? - Ozkan, Turgut (American journal of criminal justice, 2016)
Following recent high-profile deaths of unarmed African American suspects at the hands of police, a number of reforms have been proposed, among them improved minority representation in the ranks of law enforcement organizations. Previous research has explored the effects of minority representation on complaints against the police and other behaviors, but very few studies have examined violence toward the police. We merged several data sources together and tested the hypothesis that minority representation within police departments is inversely associated with assaults against the police. In an extension of prior research, we also conducted separate analyses for African American, Hispanic, and Asian officer representation. The results did not support the expectation that diversity within police organizations results in improved police-citizen interactions, as measured by assaults on police. This study is one of the few to examine how different measures of minority representation in police agencies relates to assaults on the police.